Prevalence of reproductive conditions in canines - JOSEPH, CECILIA; KULASEKAR, K; ARAVIND, AMRITHA; THILAGAR, S (The Indian Journal of Animal Reproduction, 2005)
The prevalence of reproductive conditions in canines were analysed from 2498 clinical cases presented to the SmallAnimal Gynaecology and Obstetrics Unit of Madras Veterinary College hospital during the year 1999 to 2001. The incidence ofphysiological conditions (61.9%) like breeding advice and pregnancy diagnosis were higher than the pathological disorders(38.1%) like pseudopregnancy, anestrum, medical termination of pregnancy, pyometra, dystokias, postpartum conditions andvenereal tumors. Higher incidences of reproductive conditions were recorded during South West Monsoon (27.94%). Majority ofthe reproductive problems occurred in bitches aged 1 to 2 years (42.31 %) and in the Spitz breed (38.71 %).
Keywords: Incidence; Reproductive disorders; canine